Neuroscience and neurophilosophical rethinking in the solution of the body-mind problem - Puma-Romero, Manuel J. (2021)
The relationship between the body and the mind has been and still is a persistent dilemma that continues today after centuries of continuous discussions. Both, philosophers, and doctors have advocated diverse theories, with a myriad of questions, and various schools of thought that seek to answer the problem. This review is based on the following question: If we understand the origins of the relationship between body and mind, would the solutions be found in the fields of neuroscience and neurophilosophy? The etymology of the terms, mainly the prefixes “neuros”’ and “psyche”, is studied to delve into the Cartesian conception of the res cogitans and the res extensive. Based on the seven steps of philosophical research, this essay attempts to elucidate the essence of this scientific and philosophical problem contrasting dualism and monism, considering the material and spiritual levels, and embracing the concept that the mind is a product of the brain.